Modifying Spinel Precursors for Highly Active and Stable Ni‐based CO2 Methanation Catalysts - Weber, Dennis; Wadlinger, Katja Marion; Heinlein, Maximilian; Franken, Tanja (ChemCatChem, 2022)
In CO2 methanation, spinel phases are often considered as undesirable leading to deactivation. However, they can also be considered as well-dispersed solid solutions suitable as catalyst precursors leading to the formation of highly active and finely dispersed active sites. Though, spinels such as NiAl2O4, which form when Ni/Al2O3 supported catalysts are used, require high reduction temperatures to become active. To obtain a suitable catalyst precursor, the reducibility of such spinels must be improved so that it can be activated under conventional conditions. The undesirable spinel phase is modified by introducing manganese, known to distort the spinel structure, to form Ni0.9MnxAl2-xO4 (0≤x≤2) as a new catalyst precursor. These exhibit significantly improved reducibility at low temperatures. By adjusting the manganese content, a methane yield of 38.7 % was achieved at 350 °C under the conditions used, which is more than twice that of the supported Ni/Al2O3 reference catalyst (SPP2080-IMRC
CRIS-Team Scopus Importer:2022-08-26
Keywords: Catalysis; CO; Mixed metal oxides; Spinels

Synthesis of methanol by hydrogenolysis of biobased methyl formate using highly stable and active Cu-spinel catalysts in slurry and gas phase reactions - Haagen, Vera; Iser, Jakob; Schörner, Markus; Weber, Dennis; Franken, Tanja; Wasserscheid, Peter; Schühle, Patrick (Green Chemistry, 2023)
This contribution deals with a new atom efficient two-stage production route for green methanol (MeOH) from biomass that includes biomass conversion to methyl formate (MF)/formic acid (FA) mixtures followed by hydrogenolysis to MeOH. Herein, we focus on the hydrogenolysis step and propose a materials solution to the problem of catalyst corrosion by the acidic MF/FA mixture formed in the previous biomass oxidation step. We show that Cu0.9Al2O4 spinel materials are very effective hydrogenolysis catalysts for the conversion of MA/FA mixtures to MeOH. Compared to commercial catalysts such as CuO/Cr2O3, the spinel material does not contain hazardous chromium compounds or require them during synthesis. Furthermore, this spinel catalyst shows much lower corrosion than known commercial hydrogenolysis catalysts. By using reactive frontal chromatography, nitrogen sorption, IR-ATR and XRD measurements we show, that CuO/MgO/ZnO/Al2O3 and CuO/Cr2O3 suffer from leaching of copper and chromium in the presence of FA due to the formation of mobile metal formate species. In contrast, the strongly fixed nature of copper in the highly ordered crystal structure of our Cu0.9Al2O4 spinel type catalyst leads to exceptional stability in the presence of FA and in continuous hydrogenolysis experiments for more than 110 h time-on-stream.<br